Experiences of deaf women and girls in accessing maternal health rights and services in Uganda - Esther M.A. Gimono (African Journal of Disability, 2025)
Background: Women with disabilities are at disproportionate risk for adverse pregnancy outcomes partly because of the limited information on their pregnancy histories. However, deaf women are faced with communication challenges, sexuality, menstrual health as well as pregnancy and its care, which remain a contemporary phenomenon. Still, little is known about the lived experiences of deaf women and girls.